Quality of work life (QWL) situation in the Nepalese corporate sector (Quest Journal of Management and Social Sciences, 2019)
Background: Existing literature on QWL and CG supports that effective compliance of CG is dependent on how the institution is nourished with the spirit of QWL and CG maintains relationship between the company’s management, board of directors, shareholders, employees, and auditors and stakeholders. Moreover, QWL consider different components like autonomy of work, compensation and rewards, job satisfaction and job security, quality of work life, relation and co-operation, training and development, work environment.Objectives: The main purpose of this paper was to investigate the factors, dimensions and policy implications to foster quality of work life (QWL) situation in organizations, especially in the Nepalese corporate sector.Methods: Fully based on qualitative desk review and analyses.Results: This paper has attempted to establish relationship between the determinants of QWL situation and corporate governance (CG) from a positivists’ perspective. In the present Nepalese context, several challenging factors, such as, employee attitude, working environment, opportunities, nature of work, stress, job challenges, development and career potential are affecting QWL attainment.Conclusions: QWL promotes adequate and fair compensation, safe and healthy working condition, opportunity to use and develop human capabilities, opportunity to growth and security, social integration, constitutionalism, social relevance of work life; work and total life span of the people.Implications: Robust QWL standardization, monitoring and evaluation be in place to govern all corporate entities in a meaningful manner.